(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Virtual means is a software package that allows physical experiments to be carried out on a computer without direct contact with a real laboratory setup or stand. The article discusses the main cognitive research of the application and effectiveness of virtual tools in the education system.